Effect of supplemental dietary phytogenic blends on growth performance, jejunal histomorphometry, and jejunal immunity of broiler chickens - A. Ceylan; P. Saçaklı; Ö. Özgenç Çınar; M. S. Ramay; U. Ahsan; U. Ahsan; J. A. Harijaona; A. G. Bayraktaroğlu; F. Manghebati; A. Calik (Archives Animal Breeding)
This study evaluated the effects of two phytogenic blends on broiler performance, intestinal histomorphology, CD4+ (cluster of differentiation) and CD8+ T-cell numbers, and mRNA abundances of several cytokines in broilers. For this purpose, a total of 300 Ross 308 male broiler chicks that were 1 d old were randomly allocated to five experimental groups. The control group was fed a basal diet without any additives, and there were two phytogenic supplement groups (blend A, mainly comprising extracts of Thymus vulgaris and Filipendula ulmaria, and blend B, consisting of Ginkgo biloba and Silybum marianum) with two dosage regimens each (100 and 200 mg kg−1 (denoted A100 and A200) and 100 and 300 mg kg−1 (B100 and B300) of the diet, respectively). Over the total growing period, body weight gain and feed intake were unchanged among the groups, although phytogenic blend B showed a dose-dependent improvement in feed conversion ratio. Both phytogenic blends did not affect carcass characteristics. Jejunal morphology (villus height, crypt depth, and their ratio) was modified depending on both the composition and the dosage levels of the selected phytogenics. Also, both phytogenic blends linearly increased the CD4+ and CD8+ T-cell numbers in the jejunum. Moreover, no major treatment effects were observed on mRNA abundances of cytokines (IL-1β, IL-6, and TNFα). However, across the two phytogenic additives employed, a positive linear dose response in IL-1β abundance was noted on day 21 in broilers fed phytogenic blend B. Overall, dietary phytogenic blend B improved the intestinal health and growth performance of chickens compared to blend A. Further studies are suggested to elucidate the effects of the tested phytogenic blends on gut microbiome and on oxidative stress in broiler chickens.